The rat race of capital structure research for REITs and REOCs: Two spotlights on leverage - Ralf Hohenstatt; Bertram Steininger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper presents a dynamic multi-equation model based on a balance sheet identity, where technical aspects of capital structure are highlighted through separately observing debt and equity and their relationship to investment. Additionally, leverage dynamics are interpreted in their role for liquidity management. Interactions of leverage with lines of credit (LOC) and cash are considered in the light of financial flexibility. The major findings obtained by observing US REITs and REOCs from 1995 to 2010 are as follows. In accordance with the existing literature, cash and LOC reveal a substitute relationship. However, the calculus of financial flexibility and our findings suggest that leverage positively drives cash, which is consistent with Gamba and Triantis (2008), and also with the accepted perspective of debt minus cash being net debt (Spotlight A). Consequently, the very robust results indicate that leverage eliminates a significant amount of information. Further mechanical relationships, especially for market leverage, are suggested (Spotlight B).
Keywords: G32; G33; G35; 330; capital structure; Real Estate Investment Trust (REIT); Real Estate Operating Company (REOC); financial flexibility; cash flow sensitivities; leverage ratio; lines of credit; cash & cash equivalents; Immobilienfonds; Kapitalstruktur; Betriebliche Liquidität; Kredit; USA